Pemberdayaan Masjid Sebagai Sarana Pendidikan Islam Bagi Remaja Masjid Al–Ittihad Pulo Brayan Bengkel - Ramli, Nazmi Lailina; Fanreza, Robie (Universitas Labuhanbatu, 2023)
In the context of mosque empowerment research as a means of Islamic education for mosque youth which shows how in managing mosques as a means of education that mosques are not just places of worship but places of application of knowledge, namely Islamic education. This study aims 1) to find out the role of BKM in empowering mosques as a means of Islamic education for young people at the Al-Ittihad mosque, 2) to find out what activities are carried out by BKM in empowering mosques as a means of Islamic education for young people at the AlIttihad mosque, 3) To find out what factors hinder mosque empowerment activities as a means of Islamic education for young people at the Al-Ittihad mosque. This type of research is qualitative research. Data collection techniques in this study are observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, drawing conclusions. After the research was carried out, the results obtained were that the Kenaziran Mosque Agency (BKM) played a very important role in every activity related to the mosque, the role of BKM was very strategic in the formation of religious youth in mosques and as a efforts to develop good morals by involving them directly in various activities in the mosque.